A espacialidade na escultura do séc. XX : do espaço fechado ao espaço negativo - Gonçalves, Diogo Pereira da Silva, 1990- (2018)
In this Master in Sculpture Studies we try to expose and analyze the question of space in sculpture, from the beginning of modernism to the present day, mentioning some close previous situations and following R. Krauss logic of expanded space in sculpture. In this sense, we look to a better understanding of how to transit from a closed space to a negative one, through the history of sculpture of the 20th century. Enunciating these same changes, focusing on the different approaches made before, from analyses of both artists thoughts, as well as artist’s deposition on writings and interviews among other sources. We wish above all, not loose sight of the relation’s between, artist, work of art and spectator, having has main concern the historical-conceptual dimension of the works of art in relation with space